Teacher's work under constant stress is a current trend - Garmash, Sergii Volodymyrovych (Одеський національний економічний університет, 2025)
The purpose of the article is to highlight problematic issues in the country’s higher education system, namely, to analyze the situation that has developed in the higher education system in recent years, to trace the trends that have emerged in their dynamics, to identify the root causes and possible consequences of these trends. We are talking about the work of teachers in a constant state of stress, which is a negative trend today. The consequence of teachers working in such conditions is the emergence of a professional burnout syndrome, which may be a planned process of artifiial reduction of the teaching staff The assumption presented in the article is supported by examples of constant changes in the requirements for teachers in accordance with the Licensing Conditions for Educational Activities, which complicate their implementation. Several factors contributing to professional burnout of teachers were analyzed, namely: 1) lack of time to perform professional functions against the background of increasing volumes of work with documentation; 2) work overload, exceeding the norm of working hours; 3) low level of material motivation with signifiant volumes of work performed. In an environment where the concept of “higher education standards” is being replaced by the concept of “standardization of higher education”, attention should be paid to the widespread use of digital technologies in the fild of education. It is announced that digital educational technologies are understood as the use of various electronic tools and software to improve the quality of learning and ensure access to knowledge for students andteachers. The article also attempted to draw attention to a new current trend – digitalization, which has both its advantages and disadvantages in education. This trend confiently entered the educational space with the COVID-19 pandemic and the spread of hostilities in the country. It is noted that the comprehensive digitalization of the educational process is gaining momentum, which can lead to unpredictable negative consequences for both the individual and society as a whole. While working on the article, the methods of observation and comparison, the method of expert assessments, the method of unity of analysis and synthesis, and the modeling method were used. Метою статті є висвітлення проблемних моментів у системі вищої освіти країни, а саме – аналіз ситуації, яка склалася в системі вищої освіти за останні роки, простеження тенденцій, що намітилися в їхній динаміці, виявлення першопричин та можливих наслідків цих тенденцій. Ідеться про роботу викладачів у постійному стресовому стані, що є негативним трендом сьогодення. Наслідком роботи педагогів у таких умовах є виникнення синдрому професійного вигорання, що може бути спланованим процесом штучного скорочення викладацького складу. Наведене припущення в статті підкріплюється прикладами постійних змін у вимогах до викладачів відповідно до Ліцензійних умов провадження освітньої діяльності в сторону ускладнення їх виконання. Проаналізовано декілька чинників, які сприяють професійному вигоранню педагогів, а саме: 1) дефіцит часу для виконання професійних функцій на тлі збільшення обсягів роботи з документацією; 2) робочі перевантаження, перевищення норми тривалості робочого часу; 3) низький рівень матеріальної мотивації за значних обсягів виконуваної роботи. В умовах, коли поняття «стандарт вищої освіти» підмінюється поняттям «стандартизація вищої освіти», варто звернути увагу на широке застосування цифрових технологій у сфері освіти. Анонсується, що під цифровими освітніми технологіями розуміють використання різноманітних електронних засобів та програмного забезпечення з метою покращення якості навчання й забезпечення доступу до знань здобувачам освіти та викладачам. У статті здійснено спробу привернути увагу до нового тренду сьогодення – до цифровізації, яка в освіті має як свої переваги, так і недоліки. Цей тренд впевнено увійшов в навчальний простір з пандемією COVID-19 та з поширенням бойових дій на території країни. Відмічається, що комплексна цифровізація навчального процесу набирає обертів, що може призвести до непередбачуваних негативних наслідків як для особистості, так і для суспільства загалом. Під час роботи над статтею використано методи спостереження та порівняння, метод експертних оцінок, метод єдності аналізу та синтезу, метод моделювання.
Робота викладача в постійному стресі як тренд сьогодення
Keywords: stressful state; burnout syndrome; lack of time; work overload; lack of motivation; interconnected processes; negative selection; digitalization of the educational process; negative consequences; стресовий стан; синдром професійного вигорання; дефіцит часу; робочі перенавантаження; відсутність мотивації; взаємопов'язані процеси; негативна селекція; цифровізація навчального процесу; негативні наслідки